Developing a Profiling Methodology for Displaced People in Urban Areas - Jacobsen, Karen; Furst Nichols, Rebecca (Tufts Archival Research Center, 2014)
In seeking to develop effective programmatic interventions, it is useful for humanitarian agencies to understand whether displaced people in urban areas are worse off than the urban poor and other migrants amongst whom they live. There is controversy around this issue. A widely held belief is that refugees and IDPs are worse off in urban settings, because they have lost their assets and social networks, and lack secure housing, land and property rights, and the cultural knowledge required to survive in a city. Others have argued that refugees are not necessarily more vulnerable than other migrants, and these differences are eroded over time. In particular, some research suggests that international migrants, including refugees, are often better equipped to deal with cities than newly urbanized citizens of the host country. Whether refugees and IDPs are more economically vulnerable and at greater risk is one of the questions we explore in this research.